Henrique e o Robô Dim: gamebook para apoiar o processo de ensino e aprendizagem de educação financeira infantil - Mello, Felipe da Cunha de (2016)
Nowadays, there are great governmental and educational institutions efforts to promote financial education in Brazil, driven by social and economic politics which have been adopted in this country. At the same time, there is a notable technological evolution and encouragement of information and Communication Technologies (ICT) didactics and pedagogical tools in school routine. Therefore, this scientific dissertation presents an investigation of how a gamebook can promote the financial education learning in childhood. Through a survey, characterized as exploratory using bibliographic review, it was possible to feature childhood financial education area as well as identify how it is applied at schools in Santa Maria/RS. As a result, it was obtained requirements in order to develop a learning object which could be used as a financial education disseminator. Thus, with this research it was observed that the construction of knowledge in finances has been permeated by several technological and media tools. However, the main resource which is being used to attract child attention is ludic activities. In addition, a way to work with ludic activities is the integration of game elements with book characteristics, connecting tradition and technology, in order to follow this new reality. Wherefore, considering this association it was decided to develop a gamebook, attractive tool for education, migrating from physic book to digital book. It was elaborated the gamebook "Henrique and the robot Dim" throughout a construction of a narrative presenting situations of financial choosing, creation of digital scenarios and characters, and the integration of the narrative with the digital environment and game elements. As a purpose of evaluating this gamebook, it was applied on students of fifth grade from both private and public schools in Santa Maria/RS. As a result, it was observed that the technology as a teaching tool enhances student participation during class, mostly when educational ludic activities are applied. In addition, it was noticed a possible increased student's financial education interest. This dissertation is part of Stricto Sensu Post-Graduation Program in Educational Technologies in Networks, with area of interest in Educational Technologies development, and has developed the gamebook called "Henrique and the robot Dim"